A federalism that still struggles to be born (Cultura Económica, 2019)
The recognized Argentine economist Juan J. Llach dedicates this article to the current issue of federalism. The article describes some present aspects of the regional economies, and the problem of fiscal responsibility. Though today a very important rebirth of the regional economies is taking place, the different governments continue delaying the establishment of a fiscal system of federal co-participation that yields the tributary responsibilities to theprovincial governments. Llach offers his view on the reasons for this delay, and on the factors that sustain them. On the other hand, he also indicates that it would be a great mistake to fail in taking advantage of the moment that the country is going through.
Keywords: federalism; co-participation; beneficiary interests; power of taxation